Application of Fuzzy FMEA to Rainfed Lowland Rice Production in Sarawak: Environmental, Health and Safety Perspectives - Anisia, Jati Sang (Universiti Malaysia Sarawak (UNIMAS), 2019)
Rainfed lowland rice is the most favorable method for rice cultivation in Sarawak, Malaysia. Overall, rice production in Sarawak consists of seven sub-processes, namely preparing land, establishing crop, transplanting, managing crop, harvesting, post-harvesting, and milling. Majority of farmers in Sarawak rely on their indigenous knowledge and experience for rice cultivation. There are a number of guideline available for rice production system, which are useful to assist farmers in their farm. However, those existing guideline is still poorly synchronised with the local rice production industry. Hence, in this thesis, fuzzy Failure Mode and Effect Analysis (FMEA) which is an advanced quality and risk assessment methodology, is used as a knowledge-based tool to support rice production in Sarawak. The concern in this research is on the assessments of health, safety and environment aspect to farmers and consumers. With the support from the Sarawak Government, the data and information pertaining to various failure occurred, the root causes and current detections method were studied. In short, a fuzzy FMEA methodology was developed to improve yield and enhanced food safety, therefore, this work may contributing towards modernization of the rice production industry in Sarawak. Specifically, fuzzy FMEA is adopted to inculcate the best practices for farmers to improve yield and enhance food safety. Through this study, it was identified that musculoskeletal disorders due to bad postures is the most noticeable occupational health hazard. The practice of good posture could reduce the O ratings from 7 to 5; resulted reduce standard Risk Priority Number (RPN) score from 126 to 90 and reduce Fuzzy Risk Priority Number (FRPN) score from 779 to 691. Apart from that, a new techniques and tools were invented and introduced to mitigate this risk.